Optimizing Post-CDK4/6i Strategies In HR +/HER2− Advanced Breast Cancer: A Contemporary Evidence-Based Framework - Teena Rajan; Amol Akhade (Indian Journal of Medical and Paediatric Oncology)
The advent of CDK4/6 inhibitors has transformed the frontline management of HR +/HER2− metastatic breast cancer. However, resistance to these agents is inevitable, leading to a growing need for evidence-based post-progression strategies. This review synthesizes data from major trials—SONIA, PALMIRA, MAINTAIN, postMONARCH, and EMBER-3—exploring both rechallenge and class-switching strategies. We evaluate the clinical impact of switching versus continuing CDK4/6 inhibitors, mechanisms of resistance, and emerging agents such as oral SERDs (selective estrogen receptor degraders) and PROTACs. The evidence suggests limited benefit for same-agent rechallenge and supports the use of novel combinations in biomarker-selected populations. Personalized sequencing guided by molecular profiling may define the next frontier in HR +/HER2− metastatic breast cancer management.